The Role of Government Effectiveness Boosting The Influence of Financial Development and International Trade in ASEAN-5 Country - Humanita, Salwa Nabella Aksi; Endraswati, Hikmah (Jurnal Ilmu Ekonomi Terapan, 2024)
The main focus of this study is the crucial role of an effective government in managing financial development and its impact on international trade. This study aims to analyze the effectiveness of government intervention in moderating the effect of financial development on international trade in the ASEAN-5 region. Annual panel data covering the period 1997-2023 of ASEAN-5 countries will be used in the analysis. The proposed analysis method is Panel Data Regression and Moderated Regression Analysis (MRA) using EViews version 10. The results show that financial development measured using the proxy of bank deposits and liquid liabilities can significantly affect international trade. In contrast, when measured using bank credit, it has a significant negative effect. Government effectiveness can strengthen the influence of bank credit and liquid liabilities on international trade. In contrast, bank deposits can weaken it because the effectiveness of the government in regulating and developing the financial system can interfere with the openness of international trade.